PELATIHAN MINDFULNESS UNTUK GURU SEKOLAH DASAR DI KABUPATEN BADUNG - Wilani, N.M.A.; Fridari, I.G.A.D.; Suarya, L.M.K.S.; Mogi, I.K.A. (Buletin Udayana Mengabdi; Vol 23 No 2 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i02.p01, 2023)
This community service activity aims to provide additional knowledge and mindfulness skills to teachers in elementary schools in the Badung regency. The service team expects teachers who practice mindfulness to prevent work burnout, develop more positive emotions, and have self-help supplies to reduce personal stress. The training activities are carried out in two forms, online and outside the network, focusing on psychoeducation and mindfulness practices. A total of 40 teachers from various school representatives attended the training activities. The face-to-face training activities took place at SD No. 3 Sempidi. This activity results in the teachers' understanding of mindfulness increasing. The teacher can practice several mindfulness techniques. The teacher can choose the mindfulness technique that is deemed suitable and get benefits from the training. The service team hopes that mindfulness training results can provide hands-on experience related to mindfulness and its various benefits for elementary school level teachers in the Badung regency. Keywords: Badung Regency, Teacher, Mindfulness, Training, Elementary School.